Applying the Model Driven Architecture Approach for Geographic Database Design using a UML Profile and ISO Standards - Nalon, Filipe Ribeiro; Filho, Jugurta Lisboa; Braga, José Luís; Borges, Karla Albuquerque de Vasconcelos; Andrade, Marcus Vinícius Alvim (Journal of Information and Data Management, 2011)
In the last 20 years, several conceptual data models specific for Geographic Information Systems (GIS) have been proposed. However, so far there isn’t a consensus model, which has generated several problems for the GIS area, such as the lack of interoperability among CASE tools that give support to these models. A UML profile, called GeoProfile, was proposed to standardize the task of geographical data modeling. The GeoProfile was designed based on the main models for geographic database in the literature, seeking to support some requirements for geographic applications modeling. This paper describes the use of Model Driven Architecture approach (MDA) in the design of geographic databases, using the GeoProfile aligned with international standards of ISO 19100 series. The paper also shows that with the automatic transformation of models is possible from a conceptual scheme with a high level of abstraction to achieve the generation of scripts for spatial databases.